2011
DOI: 10.17660/actahortic.2011.897.61
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Banana Plants Resistant to Banana Bunchy Top Virus Infection

Abstract: Embryogenic cell suspensions (ECS) initiated from immature male flowers of banana cultivar 'Dwarf Brazilian' (AAB, Pome subgroup) were transformed using Agrobacterium tumefaciens containing one of four constructs derived from the replicase-associated protein (Rep) gene of the Hawaiian isolate of Banana bunchy top virus (BBTV). Each construct was engineered under control of a double CaMV 35S promoter and the AMV enchancer sequence in the binary plasmid pBI121. Constructs were transferred into A. tumefaciens str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 19 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…BBTV transmission studies through aphids under greenhouse conditions. Bioassay to screen the transgenic banana and symptom expression observation made on transgenic and non-transgenic bananas (Borth et al, 2011;Elayabalan et al, 2013).…”
Section: Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…BBTV transmission studies through aphids under greenhouse conditions. Bioassay to screen the transgenic banana and symptom expression observation made on transgenic and non-transgenic bananas (Borth et al, 2011;Elayabalan et al, 2013).…”
Section: Transmissionmentioning
confidence: 99%
“…In 2011, it was reported that some transformed clones of 'Dwarf Brazilian' (AAB, Pome subgroup) were resistant to BBTV under experimental conditions in Hawaii (Borth et al, 2011). Two Indian research groups have claimed success.…”
Section: Recent Bbtv Resistant Banana Clone Development Through Rnai mentioning
confidence: 99%
“…Further, no pathogen-derived resistance strategies have been reported to be fully efficacious in imparting resistance against BBTV infection in banana. Recently, Borth et al (2011) have succeeded in generating banana plants resistant to BBTV using the viral Rep gene. They have used a variety of constructs based on BBTV Rep gene sequence and its regulatory regions to achieve this resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Also, transgenic papaya plants with the mutated replicase (RP) gene from PRSV showed high resistance or immunity against PRSV in the field (Xiangdong et al 2007). Borth et al (2011) developed transgenic banana (cv. Dwarf Brazilian) plants resistant to banana bunchy top virus (BBTV) by transforming four gene construct derived from the replicase associated protein (Rep) gene of the Hawaiian isolate of BBTV.…”
Section: Virus Resistancementioning
confidence: 99%